Pengaruh Periklanan Dan Sikap Konsumen Terhadap Minat Beli Pada Store Eiger Seberang Ulu II Kota Palembang (Jurnal Manajemen dan Investasi (MANIVESTASI), 2024)
ABSTRACT This study aims to determine the effect of advertising on buying interest, the influence of consumer attitudes on buying interest, and the influence of advertising and consumer attitudes on buying interest. The method used in this study is a quantitative method with the number of samples studied is 60 respondents, namely consumers who come to Store Eiger. This research instrument test uses validity and reliability tests, data analysis techniques in this study use classical assumption test methods consisting of normality test, multicollinearity test, heteroscedasticity test, simple linear regression analysis test, multiple linear regression test, coefficient of determination test and hypothesis testing. which consists of t test, and F test. Hasi; The t test partially concludes that there is an influence between the advertising variable on buying interest with a significant value of 0.000